Opportunities and Challenges For RCTV In Maintaining The Existence Of The “Wewara” Program - Dwi Lestari; Siti Khumayah; Dedet Erawati (Indonesian Journal Publisher, 2026)
This study aims to examine the opportunities and challenges faced by Radar Cirebon Television (RCTV) in maintaining the existence of its news program, Wewara, amid the rapid development of media convergence in the digital era. The study is motivated by changes in public media consumption patterns, where audiences increasingly prefer digital platforms over conventional television broadcasting. This condition requires local television stations to adapt their strategies to remain relevant and competitive in the media industry. This research employed a qualitative approach using a case study method to obtain an in-depth understanding of the phenomenon. Data were collected through in-depth interviews with key informants, including the Editor-in-Chief, reporters, and two viewers of the Wewara program. Observation and documentation techniques were also used to support data validity and enrich the findings. The collected data were analyzed descriptively to identify the implementation of media convergence and the challenges encountered by RCTV. The findings indicate that RCTV has implemented various media convergence strategies by utilizing digital platforms and social media as alternative channels for content distribution and audience engagement. These efforts provide opportunities to expand audience reach and maintain the relevance of the Wewara program. However, the implementation of media convergence still faces several obstacles, particularly in optimizing digital strategies, adapting to technological developments, and overcoming limitations in human resources and media management. The study concludes that media convergence plays a crucial role in sustaining the existence of the Wewara program. Therefore, strengthening editorial management, enhancing digital capabilities, and continuously innovating news content are essential to Improve RCTV’s Competitiveness In The Digital Media Landscape.